What Kind of Institutional Environment Can Promote The Development of Rural Industries in China?—Based on Fuzzy Set Qualitative Comparative Analysis - Weiwei, Xu (SAGE open, 2025)
Institutional environment is the most fundamental soil for the survival and development of industries, and the synergistic effect of institutional environment factors can help the development of rural industries. The article uses the marketization index related data of 31 provinces (autonomous regions, municipalities directly under the central government) in China in the year of 2019, and adopts the fuzzy set qualitative comparative analysis method (fsQCA) to explore the path of institutional environment driving rural industrial development from the perspective of configuration. The results of the study show that: (1) One single institutional environment factor is not a necessary condition for generating high efficiency of rural industries. (2) The development of rural industries is influenced by multiple institutional environment factors, which are “multiple and concurrent” to form diverse groupings, that is, to promote the development of rural industries in the way of “different paths to the same destination.” (3) There are two types of institutional environment groupings that can enhance the efficiency of rural industries: legal environment-driven type and product market-driven type. The significance of this study is that analyzes the impact of the interaction of various institutional environment factors on rural industrial development, enriches the research on rural industrial development, and reveals the complex causal mechanism of the institutional environment in promoting rural industrial development.